Treatment of monogenic and digenic dominant genetic hearing loss by CRISPR-Cas9 ribonucleoprotein delivery in vivo - Yong Tao; Veronica Lamas; Wan Du; Wenliang Zhu; Yiran Li; Madelynn N. Whittaker; John A. Zuris; David B. Thompson; Arun Prabhu Rameshbabu; Yilai Shu; Xue Gao; Johnny H. Hu; et al. (Nature Communications, 2023)
Abstract Mutations in Atp2b2, an outer hair cell gene, cause dominant hearing loss in humans. Using a mouse model Atp2b2 Obl/+, with a dominant hearing loss mutation (Oblivion), we show that liposome-mediated in vivo delivery of CRISPR-Cas9 ribonucleoprotein complexes leads to specific editing of the Obl allele. Large deletions encompassing the Obl locus and indels were identified as the result of editing. In vivo genome editing promotes outer hair cell survival and restores their function, leading to hearing recovery. We further show that in a double-dominant mutant mouse model, in which the Tmc1 Beethoven mutation and the Atp2b2 Oblivion mutation cause digenic genetic hearing loss, Cas9/sgRNA delivery targeting both mutations leads to partial hearing recovery. These findings suggest that liposome-RNP delivery can be used as a strategy to recover hearing with dominant mutations in OHC genes and with digenic mutations in the auditory hair cells, potentially expanding therapeutics of gene editing to treat hearing loss.